2021
DOI: 10.1371/journal.pntd.0009685
|View full text |Cite
|
Sign up to set email alerts
|

A spatio-temporal analysis of scrub typhus and murine typhus in Laos; implications from changing landscapes and climate

Abstract: Background Scrub typhus (ST) and murine typhus (MT) are common but poorly understood causes of fever in Laos. We examined the spatial and temporal distribution of ST and MT, with the intent of informing interventions to prevent and control both diseases. Methodology and principle findings This study included samples submitted from 2003 to 2017 to Mahosot Hospital, Vientiane, for ST and MT investigation. Serum samples were tested using IgM rapid diagnostic tests. Patient demographic data along with meteorolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 28 publications
3
21
2
Order By: Relevance
“…Previous studies showed that temperature was an important factor affecting the incidence of scrub typhus, which was consistent with our discovery ( 10 , 27 ). The analysis found that the lag effect was obvious when the monthly mean temperature was higher, and the risk of disease increased with temperature.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies showed that temperature was an important factor affecting the incidence of scrub typhus, which was consistent with our discovery ( 10 , 27 ). The analysis found that the lag effect was obvious when the monthly mean temperature was higher, and the risk of disease increased with temperature.…”
Section: Discussionsupporting
confidence: 93%
“…and Orientia spp. are similarly projected to increase over the coming years (32,33). Several zoonoses arising in SEA have also come to recent attention due to the severity of their associated clinical syndromes, and/or their pandemic potential.…”
Section: Southeast Asia -At the Confluence Of Endemic Emerging And Resurgent Infectious Diseasesmentioning
confidence: 99%
“…Climate change may lead to changes in the environment which affect host and vector abundance and as a result impact on disease incidence. In a longitudinal study (2003 to 2017) from the Lao PDR, trends of murine and scrub typhus incidence were associated with temperature and rainfall respectively, suggesting that global heating and increased precipitation may expand the distribution and burden of these diseases 20 .…”
Section: Vector-borne Diseasesmentioning
confidence: 99%